The characteristics and clinical course of patients with melioidosis and cancer. - Tej Shukla; Simon Smith; Kristoffer Johnstone; Patrick Donald; Josh Hanson (PLoS Neglected Tropical Diseases)
Background Patients with an active cancer are more likely to develop melioidosis, but the characteristics and clinical course of melioidosis in patients with cancer have not been examined in detail. Trimethoprim/sulfamethoxazole (TMP-SMX) prophylaxis is prescribed to prevent melioidosis in patients receiving immune suppressing anti-cancer therapy in some jurisdictions-and is recommended in national Australian guidelines-however the risks and benefits of this strategy are incompletely defined. Methods The study took place in Far North Queensland (FNQ) in tropical Australia. The characteristics and clinical course of patients with melioidosis diagnosed in the FNQ region between January 1, 1998, and June 1, 2023, who had-and did not have-an active cancer were compared. We also determined the subsequent incidence of melioidosis in patients receiving immune suppressing anti-cancer therapy in the FNQ region between January 1, 2008, and June 1, 2023, who did-and did not-receive TMP-SMX chemoprophylaxis for Pneumocystis jirovecii infection. Results An active cancer was present in 47/446 (11%) cases of melioidosis diagnosed between January 1, 1998, and June 1, 2023; there was no association between melioidosis and any cancer type. Patients with melioidosis and cancer were more likely to be older (odds ratio (OR) (95% confidence interval (CI): 1.05 (1.03-1.08) P<0.0001) and immunosuppressed (OR (95% CI): 11.54 (5.41-24.6), p<0.0001) than patients without cancer. Immune suppressing anti-cancer therapy had been prescribed to 17/47 (36%) in the 12 months prior to their diagnosis of melioidosis. Only 10/47 (21%) with cancer and melioidosis in the cohort had received no immune suppressing anti-cancer therapy and had no other risk factors for melioidosis. Twelve months after the diagnosis of melioidosis, 25/47 (53%) were still alive; 9/22 (41%) deaths were due to melioidosis and 13/22 (59%) were due to the underlying cancer. Between 2008 and June 2023, there were 4400 individuals who received myelosuppressive anti-cancer therapy in the FNQ region. There was no significant difference in the incidence of melioidosis between patients who did-and did not-receive TMP-SMX chemoprophylaxis with their myelosuppressive anti-cancer therapy (1/737 (0.15%) versus 16/3663 (0.44%); relative risk (95% confidence interval): 0.31 (0.04-2.34), p = 0.20) and no significant difference in the incidence of fatal melioidosis (0/737 versus 3/3663 (0.08%), p = 0.58). Conclusions Patients with cancer are predisposed to developing melioidosis and immune suppressing anti-cancer therapy increases this risk further. However, in this region of Australia, there was no significant difference in the subsequent development of melioidosis in patients who did-and did not-receive TMP-SMX chemoprophylaxis during their myelosuppressive anti-cancer therapy.